Literary theory an anthology - Rivkin, Julie; Ryan, Michael 1951- (John Wiley & Sons, Ltd., 2017)
"Covers all the major schools and methods that make up the dynamic field of literary theory, from Formalism to Postcolonialism."--Provided by publisher.